STUDY OF THE INFLUENCE OF PRE-CAVITATION ULTRASONIC OF TECHNICAL WATER TREATMENT ON THE DEPOSITS OF CаСO3 - Тимейчук, Орест; Куба, Віталій; Кочмарський, Володимир; Костюк, Олександр (SWorldJournal, 2022)
The effect of a pre-cavitation ultrasonic (US) field with a frequency of 22.4 kHz on technical water in a tub with a field was investigated. We determined the effect of the field on pCa and pH in the process of crystallization of CaCO3, which was initiate